Students Mathematics Learning Achievement from Mathematics Teacher Performance and Principal Managerial Competencies Point of View - Muhamad Galang Isnawan; Arief Budi Wicaksono (Universitas Tidar, 2020)
Principals and teachers are two important elements that must be at the forefront of improving the quality of students in the school. Do these two things affect learning achievement? It is what the researchers answered in this study. Therefore,this study aims to describe the influence of mathematics teacher performance and principal managerial competence on student mathematics learning achievement. The approach in this study is a quantitative (survey). The population was all mathematics teachers and public high school students in Central Lombok, about 793people. Using the purposive sampling technique obtained a sample of this study were all mathematics teachers in one of the public high schools in Central Lombok, totaling 187 people. The instruments used were mathematics teacher performance and principals managerial competency questionnaires, and computer-based national exam tests to measure student mathematics learning achievement. Data analysis was performed using a regression test, namely the t-test and the F-test, to see the effect of mathematics teacher performance and principal managerial competence (individually and together). The results showed that mathematics teacher performance affected mathematics learning achievement with a t-value of 16.295, and principal managerial competence affected mathematics learning achievement with a t-value of 18.831. Furthermore, mathematics teacher performance and principal managerial competence influence student mathematics learning achievement of public senior high school students in Central Lombok with an F-value of 211.482.